Citizenship, racial identity and nation building in South Africa - Alexander, Neville (Tempo Social, 2006)
This article examines the relationship between affirmative action as applied in post-apartheid South Africa and the concomitant perpetuation of racial identities that were shaped by the colonial and apartheid history of the country. It problematises this state of affairs and suggests an alternative, less divisive and dangerous course.